Yves Montand in the USSR cultural diplomacy and mixed messages - Oiva, Mila (Springer International Publishing, 2021)
Intro -- Acknowledgements -- About the Book -- Contents -- About the Authors -- List of Figures -- Chapter 1: Introduction -- Chapter 2: 1956: The International Background -- Post-war 1945-1955 -- 1956: A Year of Crises -- Poland -- Hungary -- Suez -- Chapter 3: The Soviet Thaw and Cultural Diplomacy -- The Onset of the Thaw -- Anomalies -- Everyday Life -- Cultural Diplomacy -- Chapter 4: Biography: Ivo Livi and Yves Montand -- From Ivo Livi to Yves Montand -- Paris -- Recording and Film Stardom -- Simone Signoret -- International Stardom -- Left-Wing Peace Activism -- Chapter 5: Preparations, Hesitations and Decisions -- Beginnings -- Delays, Obstructions and Controversies -- Soviet Preparations -- Chapter 6: The Construction and Reception of Montand's Public Image -- Pre-tour Soviet Celebrity -- Constructing Montand's Celebrity with Music and Print Media -- Montand's Tour in the Soviet Media -- Popular Reactions to the Tour -- Chapter 7: The Film Yves Montand Sings -- Preliminary Plans for the Documentary -- Experience Behind the Camera -- Arrival at Moscow -- The Film Copy and Its Structure -- Prologue (1:00-5:56, c. 5 minutes) -- Moscow (5:56-48:28, c. 43 minutes) -- Leningrad (48:28-1:02:41, c. 14 minutes) -- Kiev (1:02:36-1:13:50, c. 11 minutes) -- Silences and Absences -- Reception of the Film -- Chapter 8: The Music: Lost in Translation -- Music as 'Translation' -- Montand and the Soviet Public -- Repertoire -- Costume and Demeanour -- Content -- Advocacy for Peace -- Evocation of France -- Dissonance -- Chapter 9: Conclusions -- Appendix A: Discography of Yves Montand's Soviet-Made Recordings -- Appendix B: List of Yves Montand Postcards Printed in the USSR -- Research Literature -- Archival Collections -- Centre National du Cinéma et de l'image animée -- Gaumont Pathé Archives -- Net-Film.